Dynamic analysis of adobe structure with bilinear material modelling - Lye, Jiun Yin (2018)
Adobe structures are more vulnerable in dynamic loads especially for seismic loads. The proper material properties of the adobe bricks will provide the sufficient strength in order to minimize the damage of the adobe building and also prevent loss of human lives and save maintenance costs. In this study, the simulation method will be used by using finite element analysis software, ANSYS. This simulation study presents about structure behaviors of adobe model structures undergoes dynamic loads. The purpose of this study is to study the structure behaviour of adobe structures subjected to seismic load. Two types of difference adobe material properties will be used in this study such as nonlinear properties (adobe brick without reinforcement) and bilinear properties (adobe brick with wire mesh reinforcement). In this analysis, the structure behaviour of two difference materials like deflection, stress and strain will be compared. It is expected to find that when wire mesh reinforcement is added, the structure behaviour of adobe improves significantly. It shows that the bilinear properties (adobe brick with wire mesh reinforcement) will be more suitable to against the seismic load.